Distributed, Ambient, and Pervasive Interactions Second International Conference, DAPI 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings - Streitz, Norbert; Markopoulos, Panos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the Second International Conference on Distributed, Ambient, and Pervasive Interactions, DAPI 2014, held as part of the 16th International Conference on Human-Computer Interaction, HCII 2014, held in Heraklion, Crete, Greece in June 2014, jointly with 13 other thematically conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences were carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The 58 papers included in this volume are organized in topical sections on design frameworks and models for intelligent interactive environments; natural interaction; cognitive, perceptual and emotional issues in ambient intelligence; user experience in intelligent environments; developing distributed, pervasive and intelligent environments; smart cities.
Design frameworks and models for intelligent interactive environments -- Natural interaction -- Cognitive, perceptual and emotional issues in ambient intelligence -- User experience in intelligent environments -- Developing distributed, pervasive and intelligent environments -- Smart cities.
Keywords: User interfaces (Computer systems).; Computers and civilization; Application software; Information storage and retrieval; User Interfaces and Human Computer Interaction; Computers and Society; Information Systems Applications (incl. Internet).; Computer Applications; Information Storage and Retrieval